2020
DOI: 10.1186/s12951-020-00701-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of exosomes from whole blood by a new microfluidic device: proof of concept application in the diagnosis and monitoring of pancreatic cancer

Abstract: Background Exosomes are endocytic-extracellular vesicles with a diameter around 100 nm that play an essential role on the communication between cells. In fact, they have been proposed as candidates for the diagnosis and the monitoring of different pathologies (such as Parkinson, Alzheimer, diabetes, cardiac damage, infection diseases or cancer). Results In this study, magnetic nanoparticles (Fe3O4NPs) were successfully functionalized with an exosome-binding antibody (anti-CD9) to mediate the magnetic capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 73 publications
0
39
0
Order By: Relevance
“…These methods include ultracentrifugation, ultrafiltration, size exclusion chromatography (SEC), precipitation with polymers, and separation by affinity-based methods [47,78,79]. Recently, the devices based on microfluidic technology indicate promising advances for isolation and analysis of exosomes [80][81][82]. Therefore, look at the pros and cons of each method to find the qualified method of exosome purification is essential.…”
Section: Exosome Isolation and Purificationmentioning
confidence: 99%
“…These methods include ultracentrifugation, ultrafiltration, size exclusion chromatography (SEC), precipitation with polymers, and separation by affinity-based methods [47,78,79]. Recently, the devices based on microfluidic technology indicate promising advances for isolation and analysis of exosomes [80][81][82]. Therefore, look at the pros and cons of each method to find the qualified method of exosome purification is essential.…”
Section: Exosome Isolation and Purificationmentioning
confidence: 99%
“…Exosomes extracted from milk are absorbed in the human gastrointestinal tract in an intact form, can be delivered orally, and are expected to be used as a drug delivery system for the treatment of various diseases through the advantage of effectively delivering chemotherapy agents [ 48 , 49 ]. Blood exosomes are used as biomarkers to diagnose diseases or to monitor progression or treatment efficacy [ 50 , 51 ]. Urine exosomes can be used as a biomarker to identify the kidney and genitourinary tract, and when injected, urinary exosomes migrate to the kidney.…”
Section: Composition and Immune Modulatory Function Of Extracellulmentioning
confidence: 99%
“…Epidemiological data in 2016 showed that there were 53,070 new cases of pancreatic cancer in the United States, ranking the fourth place in the mortality of malignant tumors. In addition, the incidence rate of pancreatic cancer is increasing year by year (Sancho-Albero et al, 2020;Jiang et al, 2021). Pancreatic cancer is highly of malignant, with extremely poor prognosis (5-year survival rate less than 5%) (Goral, 2015;Heinrich & Lang, 2017).…”
Section: Discussionmentioning
confidence: 99%